Improving Collaboration Among Healthcare providers in Resource Constrained Healthcare Facilities: An Enterprise Architecture Approach - Walusimbi, Samuel; Wamema, Joseph (Journal of Health Informatics in Africa, 2022)
Background and Purpose: Application of an Information System that can provide a seamless flow of patient information and medical guidelines is highly desirable in the practice of Evidence Based Medicine (EBM). Information systems in Resource Constrained Health Facilities including Uganda have been found to be inadequate in supporting collaboration among healthcare providers. This study aimed at optimising collaboration and information sharing among healthcare providers by developing an architecture for a collaborative mobile application. Methods: The study adopted a cross-sectional research design and qualitative data was collected from 32 informants using a series of data collection methods including; interviews, focus group discussions, observation and document reviews from the hospital’s resource centre, published articles and online informatics journals. Results: Findings from this study showed that there were various information and communication systems including computers, e-mails, internet access and suffice to note, telephone calls for both landline and mobile were still being used for collaboration. Collaboration challenges that were identified include system integration issues, infrastructure limitations, data quality issues, system usability and geographical dispersals of both healthcare providers and healthcare facilities among others. The study further established that current systems focus more on monitoring and evaluation, surveillance of chronic diseases and data capture; less is done towards optimisation of collaboration. Conclusions: Healthcare providers ought to make decisions based on the most up-to-date, solid, reliable and scientific evidence, this study proposed a collaborative mobile application architecture to improve collaboration among healthcare providers at any point of care. The architecture was developed using enterprise architecture principles taking cognizance of its four crucial C’s; connection, collaboration, communication and customer.